A Conformationally Stable Acyclic β‐Hairpin Scaffold Tolerating the Incorporation of Poorly β‐Sheet‐Prone Amino Acids. (16th December 2021) - Stanojlovic, Vesna; Müller, Anna; Moazzam, Ali; Hinterholzer, Arthur; Ożga, Katarzyna; Berlicki, Łukasz; Schubert, Mario; Cabrele, Chiara
Abstract: The β‐hairpin is a structural element of native proteins, but it is also a useful artificial scaffold for finding lead compounds to convert into peptidomimetics or non‐peptide structures for drug discovery. Since linear peptides are synthetically more easily accessible than cyclic ones, but are structurally less well‐defined, we propose XWXWXpPXK(/R)X(R) as an acyclic but still rigid β‐hairpin scaffold that is robust enough to accommodate different types of side chains, regardless of the secondary‐structure propensity of the X residues. The high conformational stability of the scaffold results from tight contacts between cross‐strand cationic and aromatic side chains, combined with the strong tendency of the d ‐Pro‐l ‐Pro dipeptide to induce a type II′ β‐turn. To demonstrate the robustness of the scaffold, we elucidated the NMR structures and performed molecular dynamics (MD) simulations of a series of peptides displaying mainly non‐β‐branched, poorly β‐sheet‐prone residues at the X positions. Both the NMR and MD data confirm that our acyclic β‐hairpin scaffold is highly versatile as regards the amino‐acid composition of the β‐sheet face opposite to the cationic−aromatic one. Abstract : Open but tight : Combining the d ‐Pro‐l ‐Pro type II′ β‐turn motif with cross‐strand Trp/Lys(Arg) interactions leads to a conformationally and thermally highly stable β‐hairpin that is not sensitive to the type of residues occupying the upper face. This β‐hairpin scaffold is suited to accommodate a variety of amino acids, including poorly β‐sheet‐prone ones, and it does not require backbone cyclization